CHD and respiratory syncytial virus: global expert exchange recommendations - Tulloh, Robert; Gorenflo, Matthias (Cardiology in the young, 2017)
Background: Palivizumab is the standard immunoprophylaxis against serious disease due to respiratory syncytial virus infection. Current evidence-based prophylaxis guidelines may not address certain children with CHD within specific high-risk groups or clinical/management settings. Methods: An international steering committee of clinicians with expertise in paediatric heart disease identified key questions concerning palivizumab administration; in collaboration with an additional international expert faculty, evidence-based recommendations were formulated using a quasi-Delphi consensus methodology. Results: Palivizumab prophylaxis was recommended for children with the following conditions: <2 years with unoperated haemodynamically significant CHD, who are cyanotic, who have pulmonary hypertension, or symptomatic airway abnormalities; <1 year with cardiomyopathies requiring treatment; in the 1st year of life with surgically operated CHD with haemodynamically significant residual problems or aged 1-2 years up to 6 months postoperatively; and on heart transplant waiting lists or in their 1st year after heart transplant. Unanimous consensus was not reached for use of immunoprophylaxis in children with asymptomatic CHD and other co-morbid factors such as arrhythmias, Down syndrome, or immunodeficiency, or during a nosocomial outbreak. Challenges to effective immunoprophylaxis included the following: multidisciplinary variations in identifying candidates with CHD and prophylaxis compliance; limited awareness of severe disease risks/burden; and limited knowledge of respiratory syncytial virus seasonal patterns in subtropical/tropical regions. Conclusion: Evidence-based immunoprophylaxis recommendations were formulated for subgroups of children with CHD, but more data are needed to guide use in tropical/subtropical countries and in children with certain co-morbidities.